2021
DOI: 10.1021/acs.macromol.0c02389
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Carboxylates: Simple and Versatile Initiators for Ring-Opening Alternating Copolymerization of Cyclic Anhydrides/Epoxides

Abstract: In this contribution, we thoroughly investigated the ring-opening alternating copolymerization (ROAC) of cyclic anhydride and epoxide by using commercially available alkali metal carboxylates (AMCs) as the simple and green initiators. The idea of our work is based on the coordination effects of epoxide on an AMC and the formation of AMC–epoxide adducts, which will weaken the interaction between metal cation and its carboxylate counterion and therefore render the carboxylate to feasibly attack epoxides in a nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 71 publications
0
49
3
Order By: Relevance
“…Terminal hydroxyl group analysis indicated two ring-opening route of PO with a priority to methine carbon (Figure S49). In contrast to previous works involving the formation of polyether linkages from epoxides homopolymerization [63,65,[67][68][69] or other side reactions via isomerization of PO, [70] the ROAC of PC/PA ensured a completely alternating polyester structure owing to the slowrelease of PO despite under such a high temperature as 200 °C (Figure S50). Also, the collected gas was confirmed as CO 2 with a purity of 99.9 % by GC-MS measurement (Figure 3d), suggesting a well-defined decarboxylation reaction of PC.…”
Section: Methodscontrasting
confidence: 63%
See 1 more Smart Citation
“…Terminal hydroxyl group analysis indicated two ring-opening route of PO with a priority to methine carbon (Figure S49). In contrast to previous works involving the formation of polyether linkages from epoxides homopolymerization [63,65,[67][68][69] or other side reactions via isomerization of PO, [70] the ROAC of PC/PA ensured a completely alternating polyester structure owing to the slowrelease of PO despite under such a high temperature as 200 °C (Figure S50). Also, the collected gas was confirmed as CO 2 with a purity of 99.9 % by GC-MS measurement (Figure 3d), suggesting a well-defined decarboxylation reaction of PC.…”
Section: Methodscontrasting
confidence: 63%
“…On the basis of the above-mentioned mechanism of in situ release of PO, we proposed a strategy of ROAC of PC/ cyclic anhydrides to realize efficient utilization of PC. Owing to its high activity with epoxides in polyester synthesis, PA [63][64][65][66] was selected to demonstrate the feasibility of our strategy. The preliminary results of copolymerization of PC/ PA were summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Angewandte Chemie International Edition Figure 12: Selection of high performance CHO/PA ROCOP catalysts. [57,58,[72][73][74][75] Most catalysts active for CO2/epoxide are also active for anhydride/epoxide ROCOP, yet the reverse isn't necessarily true. For example, Lewis base catalysts only form c5c for CO2/epoxides, but catalyse anhydride/epoxide ROCOP at appropriate temperatures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, it was found that the ROAC cycle of PO/PA was faster than the ROP cycle of LA using TEB/DBU, unlike those previously reported. 33 Very recently, based on the ROAC of epoxides and anhydrides catalyzed by alkali metal carboxylates, 34 Satoh et al (2021) successfully employed these environmentally benign catalysts for the switchable ROAC and ROP of various combinations of epoxides, anhydrides, cyclic esters and initiators to achieve sequence-controlled multiblock polyesters with high effectiveness and selectivity. 17…”
Section: Introductionmentioning
confidence: 99%